How to be a star engineer. - Kelley, R.E.
Bell Laboratories hired the best and the brightest from the worlds most prestigious universities, but only a few lived up to their apparent potential for brilliance. Most developed into solid performers of mostly average productivity who did not substantially further Bell Labs' contribution to AT&T's competitive advantage in the marketplace. What the labs wanted to know was: what separates the star from the average performer? Is it innate or can star performance be learned? Could a program to improve productivity be designed that would help turn average performers into stars? Engineers from the best companies helped researchers to dispel the myths about star performers and uncover the surprising secrets of stellar achievement. To discover the secrets of star performance, the author and his colleagues used paper-and-pencil tests, direct observation, work diaries, focus groups, and individual interviews, drawing upon statistical analyses, content analyses, and iterative model building as appropriate. It was found that you need to change how you do your work and how you work with others. Star performers in fact do their work quite differently from the pack. They weave their starring strategies into a consistent pattern of day-to-day behavior. But any engineer with the necessary smarts and motivation can acquire their power. The author gives nine interlocking work strategies which can help engineers become star performers
Keywords: Bell Laboratories; Average performer; Average productivity; Content analyses; Direct observation; Focus groups; Individual interviews; Iterative model building; Motivation; Paper-and-pencil tests; Productivity improvement; Star engineer; Star performer; Statistical analyses; Work diaries; Work strategies